Effect of Microloans on the Livelihood of Beneficiaries: A Descriptive Study in Ethiopia - Diro, Bekele Abraham; Vadde, Suresh (Indian Journal of Finance, 2014)
Microcredit has been found to be a critical instrument in order to improve the livelihood of the poor. It is prominently used to improve the livelihood of the household borrowers where it is believed to be under exploited in research. Hence, it is indispensable to examine its real effectiveness and to have sufficient information on the economic and social impact indicators (human capital). For the purpose of assessing the impact of DECSI microcredit on the livelihood of borrower households, a sample of 278 respondents (that is, 123 clients who had at least 3 years of attachment to the organization and 155 eligible non-participants representing the characteristics of the existing sample borrowers) was considered for the present study. Data were collected by using a semi-structured questionnaire that was prepared and distributed for both clients and eligible non-clients and the oral interviews were conducted while the questionnaires were filled out by the respondents. The results of the study revealed that microloan participation had a positive significant average effect on households’ average monthly income, consumption expenditure, savings, and housing improvements. However, the number of employment opportunities generated for the household members showed not much of a difference. Whereas, the average effect on children’s education and medical care expenditure was positive due to the respondents’ participation in the microcredit program.